2012
DOI: 10.1111/j.1538-7836.2012.04921.x
|View full text |Cite
|
Sign up to set email alerts
|

Mortality due to pulmonary embolism, myocardial infarction, and stroke among incident dialysis patients

Abstract: Summary. Background: It is has been suggested that dialysis patients have lower mortality rates for pulmonary embolism than the general population, because of platelet dysfunction and bleeding tendency. However, there is limited information whether dialysis is indeed associated with a decreased mortality risk from pulmonary embolism. Objective: The aim of our study was to evaluate whether mortality rate ratios for pulmonary embolism were lower than for myocardial infarction and stroke in dialysis patients comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
39
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 47 publications
(58 reference statements)
5
39
0
1
Order By: Relevance
“…The prevalence of diabetes among dialysis patients differs considerably worldwide. According to the ERA-EDTA Registry, the prevalence of diabetes mellitus among dialysis patients in Europe is 22% (45), in line with the relatively low prevalence in our study population. Although the interaction analysis does show some influence of diabetes on the genetic associations, elaborate subgroup analyses are not appropriate considering the low proportion of diabetic patients in our population.…”
Section: Discussionsupporting
confidence: 85%
“…The prevalence of diabetes among dialysis patients differs considerably worldwide. According to the ERA-EDTA Registry, the prevalence of diabetes mellitus among dialysis patients in Europe is 22% (45), in line with the relatively low prevalence in our study population. Although the interaction analysis does show some influence of diabetes on the genetic associations, elaborate subgroup analyses are not appropriate considering the low proportion of diabetic patients in our population.…”
Section: Discussionsupporting
confidence: 85%
“…In agreement with Okac et al [1], we found that age, female sex and diabetes mellitus (and also hypertension, dementia, peripheral vascular disease and malignancy) were independently associated with mortality. Of course, a pivotal important difference is that the study by Ocak et al [1] studied age-and sex-mortality in patients derived from the European Renal Association -European Dialysis and Transplant Association Registry, whereas we focused on in-hospital PE-related death [3,4]. This may represent a major issue, given that the diagnosis of PE during hemodialysis is difficult, and PE ranks in second position, after coronary heart disease (7.5% of cases), among necropsy-confirmed causes of out-of-hospital sudden deaths in the general population [5].…”
supporting
confidence: 81%
“…First, the choice of identification codes: death attributable to PE was defined by ERA-EDTA code 21 in the study by Okac et al [1], and we utilized the ICD-9-CM code 415.1 to identify all subjects with emergency hospital admissions for PE. Second, in the study by Okac et al [1] older age at the beginning of renal replacement therapy (equal to or > 85 years) was associated with an increased risk of PE. However, the authors did not include co-morbidities in the analysis, and it is likely that these were more prevalent in dialysis patients.…”
mentioning
confidence: 99%
“…One previous report suggested that only about 23% of VTE-associated deaths are directly attributable to VTE, with the remaining portion being attributable to underlying diseases [2]. Nonetheless, VTE (specifically PE) has recently been reported to significantly impact mortality in adults on dialysis [33]. It is not possible to assess reasons why subjects may have dropped out of this dataset (e.g.…”
Section: Discussionmentioning
confidence: 99%